2021
DOI: 10.2147/ijgm.s308572
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori Infection in Military Personnel from Northeast China: A Cross-Sectional Study

Abstract: Helicobacter pylori infection is an important cause of peptic ulcer disease and gastric cancer. Current knowledge regarding epidemiology of H. pylori infection in military personnel has insufficiently been updated. This cross-sectional study aimed to estimate the prevalence of H. pylori infection in military personnel and to compare the prevalences in military and civilian groups. Patients and Methods: We retrospectively enrolled the subjects who underwent 14 C-urea breath tests at the Department of Gastroente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Our previous study found a higher rate of H. pylori infection in young military personnel than in civilians [ 82 ]. This phenomenon is probably explained by the fact that increased mental stress caused by high-intensity military training suppresses the body's humoral and cellular immunity, thereby increasing the risk of H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found a higher rate of H. pylori infection in young military personnel than in civilians [ 82 ]. This phenomenon is probably explained by the fact that increased mental stress caused by high-intensity military training suppresses the body's humoral and cellular immunity, thereby increasing the risk of H. pylori infection.…”
Section: Discussionmentioning
confidence: 99%
“…Gastrointestinal symptoms in recruits may be related to an increase in segmental gastrointestinal permeability during combat training (30). Military soldiers aged 17 to 25 years old need to go through numerous high-intensity training, and have a higher prevalence of Helicobacter pylori infection than civilians of the same age (31), which may cause gastrointestinal symptoms (32).…”
Section: Discussionmentioning
confidence: 99%